Pengaruh Daya Tarik dan Keahlian Social Media Influencer Terhadap Purchase Intention Pada Industri Makanan - Jessica Anggun Putri Nursetyowati; Monica Angelina; Santi Widyaningrum; Hartomy Akbar Basory (Institut Nalanda, 2023)
The influence of attractiveness and social media has several issues that will be discussed in this study. Social media is considered one of the best ways for businesses to promote their products to potential customers. Social media users seek rankings and customer reviews of specific products before making purchasing decisions. However, the increasing number of social media users has led businesses to rely on influencers as an essential element in marketing their products. This study aims to analyze the influence of attractiveness and influencer expertise on purchase intention in the food industry. The research method employed in this study is a literature review, which can serve as a consideration for food industry businesses that intend to collaborate with influencers to drive purchasing decisions.